Psychological distance increases uncompromising consequentialism - Aguilar, Pilar (2013)
Individuals can follow their moral norms, or opt for a means-end, consequentialist reasoning, in which a valuable consequence (e.g., to save the lives of five people) justifies the tolls incurred even if they clash with basic moral principles (e.g., to kill one person). Psychological distance gives rise to an abstract representation of actions that make goals more prominent and can help us ignore their immediate effects. For these reasons, psychological distance should increase consequentialism. Three experiments confirmed that different manipulations of psychological distance increased participants´ consequentialist choices, such as the killing of innocent victims in the service of valued ends.